The Survey of Malnutrition Prevalence in Patients With Parkinson Disease In Tehran, Iran - Etemad, Koorosh; Ashrafi, Farzad; Shahbazzadeh, Amir; Moghaddasfar, Tara; Arab Ahmadi, Mehran (International Clinical Neuroscience Journal, 2018)
Background: Parkinson disease (PD) introduced as the second most prevalent neurodegenerative disease following Alzheimer disease. A patient’s nutritional status may be compromising in PD. This study aimed to describe the outpatient nutritional status in patients with PD at a third-level hospital in Iran. Methods: The validated Persian version of the Mini-Nutritional Assessment (MNA) questionnaire was used to evaluate the nutritional status of 158 Iranian PD patients (age, 35-85 years). The exclusion criteria were as follows: chronic comorbidities affecting the nutritional status (e.g., diabetes and hypertension); adherence to special diets; and cognitive disorders. Based on the MNA questionnaire, a total score below 17 represented malnutrition, while scores 17-24 indicated a risk of malnutrition. Results: Based on the findings, 26% of the participants had low weight, 67% of whom were over 65 years. According to the MNA questionnaire, 14.3% of the participants showed malnutrition and 26.2% were at risk of malnutrition. Conclusion: Based on our findings, PD can contribute to reduced nutritional status. More than one-fourth of the PD population was at risk of malnutrition, which highlights the need for more attention towards nutritional assessment. Nutritional assessment is essential for the development of nutritional interventions and early detection of PD patients who are at risk of malnutrition.